Structural elucidation of fucoidan from Cladosiphon okamuranus (Okinawa mozuku) - Lim, Seng Joe; Wan Aida, Wan Mustapha; Schiehser, Sonja; Rosenau, Thomas; Böhmdorfer, Stefan (Food chemistry, 2019)
•Fucoidan from Cladosiphon okamuranus was purified for chemical structure elucidation.•The majors components of the fucoidan were fucose (70.13 ± 0.22 wt%) and sulphate (15.16 ± 1.17 wt%).•Fucoidan structure: [→3)-α-fuc(1→]0.52[→3)-α-fuc-4-OSO3-(1→]0.33[→2)-α-fuc]0.14. Fucoidan is a sulphated polysaccharide, made up mainly of l-fucose, which is found in brown seaweeds. Its chemical structure is diverse and depends on maturity, species and geographical location. The objective of this study was to elucidate the chemical structure of fucoidan from Cladosiphon okamuranus harvested in Japan. The fucoidan was subject to purification prior to monosaccharide profiling, sulphate content determination, and linkage analysis. Our results showed that Japanese Cladosiphon okamuranus fucoidan contained 70.13 ± 0.22 wt% fucose and 15.16 ± 1.17 wt% sulphate. Other minor monosaccharides found were d-xylose, d-galactose, d-mannose, d-glucose, d-arabinose, d-rhamnose and d-glucuronic acid. Linkage analysis revealed that fucopyranoside units along the backbone are linked, through α-1,3-glycosidic bonds, with fucose branching at C-2, and one sulphate group at C-4 per every three fucose units, i.e. the structure of fucoidan from Japanese Cladosiphon okamuranus is [→3)-α-fuc(1→]0.52[→3)-α-fuc-4-OSO3-(1→]0.33[→2)-α-fuc]0.14.